2009
DOI: 10.1124/dmd.108.025395
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization Is Responsible for the Structural Stability of Human Sulfotransferase 1A1

Abstract: ABSTRACT:Cytosolic sulfotransferases (SULTs) are responsible for the metabolism of a variety of drugs, xenobiotics, and endogenous compounds. Most cytosolic SULTs are found to be homodimers. However, transformation between monomeric and dimeric SULTs can be achieved by a single amino acid mutation. The importance of quaternary structure for cytosolic sulfotransferase was investigated using recombinant human SULT1A1, a homodimer, and its monomeric mutant (V270E). The differences between dimeric and monomeric SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
(27 reference statements)
4
22
0
Order By: Relevance
“…This allosteric site was identified by the ability of two substrate molecules to dock into the active site of the open hSULT2A1 enzyme [48,138]. Another report describes the loss of integrity of hSULT1A1 due to monomerization [137]. Our own observations regarding the integrity of a hSULT1B1 monomeric isoform support these results.…”
Section: The Role Of Dimerization In Sult Activitysupporting
confidence: 50%
See 1 more Smart Citation
“…This allosteric site was identified by the ability of two substrate molecules to dock into the active site of the open hSULT2A1 enzyme [48,138]. Another report describes the loss of integrity of hSULT1A1 due to monomerization [137]. Our own observations regarding the integrity of a hSULT1B1 monomeric isoform support these results.…”
Section: The Role Of Dimerization In Sult Activitysupporting
confidence: 50%
“…Despite this promising hypothesis, unpublished data now indicate that various combinations of PAPS and substrate do not affect the dimer status of hSULT2A1, implying the interface is maintained through the entire catalytic cycle of the SULTs unlike EGFR [96]. Multiple studies, including our own unpublished work involving hSULT1B1, have shown that monomeric SULT isoforms retain a high level of activity [137,138]. Aside from changes in activity levels, minimal differences between monomeric and dimeric SULT isoforms have been described.…”
Section: The Role Of Dimerization In Sult Activitymentioning
confidence: 79%
“…The same has also been observed for substrate affinity Pedersen 2002;Lu 2008;Lu 2009). Lu et al suggest that the main role for dimerization of sulfotransferases could be to maintain structural stability (Lu 2009). …”
Section: Studies Of the Dimerization Interface And The Importance Of supporting
confidence: 58%
“…Zhang et al (Zhang 1998) proposed that one of the binding sites in the hSULT1E1 dimer is catalytic and the other site is allosteric and regulates turnover. However, it has also been shown that activity, affinity and substrate inhibition are independent of subunit dimerization Pedersen 2002;Lu 2008;Lu 2009). It has been suggested that the role of dimerization is to maintain structural stability (Lu 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation